The Thin Line of Color. Representation, Stereotype and Afrodescendence in “Reportaje al Señor de los Milagros” and “Ensayo sobre la psicología del gallinazo” by Abraham Valdelomar - Leonardo Loayza, Richard (2023)
Despite the shortness of his life, Abraham Valdelomar (Ica, Peru, 1888-Ayacucho, 1919) managed to write an extensive and varied body of work in which he cultivated almost all literary genres. It is significant that in this work he barely touched upon the topic of Afro-Peruvian culture, despite belonging to this ethnic-racial affiliation himself. Valdelomar explores this theme in “Reportaje al Señor de los Milagros” (1915) and “Sobre la psicología del gallinazo” (1917). The purpose of this article is to analyze the representations of Afro-descendants and their culture presented in both texts. Our hypothesis argues that these representations do not stray from the protocol of descriptions that the West has used to solidify the identity of Afro-descendants, which are defined as hierarchically inferior beings.